(untitled) (Bangladesh Journal of Urology, 2020)
Background of the study: Urolithiasis has an incidence in the world of about 5% and the probability of a recurrence within 5–7 years is 50% (Parmar, 2004). Exact data about its prevalence is not known in Bangladesh but it is quite common as seen in outpatient department. It is more common in northern part of the country, male suffer more than female (M:F: 3:1) (Salam, 2002). Symptomatic ureteral calculi represent the most common condition encountered by an urologist in an emergency setting (Pak, 1998). Intervention is recommended for individuals with larger stones, especially greater than 5 mm (Kupeli et al., 1998). The treatment of this pathology was revolutionized with the introduction, in the late 1980s, of extracorporeal shock wave lithotripsy (ESWL), a non-invasive technology that has become one of the primary treatments for urinary stones. Its success rates vary depending on stone size and location and by the type of lithotripter employed. Medical expulsion therapy (MET) can play a key role in support of ESWL: specifically, expulsion is done by diuretics, calcium antagonists, anti-edema agents, and alpha-blockers. A few studies have reported their effectiveness (Borghi et al., 1994, Cervenakov et al., 2002, Porpiglia et al., 2002,Dellabella et al., 2003). Objective: This study is carried out to find out the role of Tamsulos in stone clearance in patientswith upper ureteral stone after extracorporeal shock wave lithotripsy (ESWL). Methods & Material: This randomized control clinical trialwas performed in Department of Urology, National Institute of Kidney Diseases and Urology, Sher-EBangla Nagar, Dhaka during the period from July 2015 to June 2017. A total of 70 cases with upper ureteric stone were included during the study period. Patients were selected randomly in every alternate sequence, odd numbers for experimental group, Tamsulosin+ ESWL, group A & even numbers for control group, only ESWL, group B. Stone clearance rate, number of ESWL session and stone expulsion time were evaluated. Results: In this study showed complete stone clearance one month after ESWL in Group A was 16(89%) and Group B was 16(84.21%) for stone size 6 to 10 mm. Comparison of clearance rate between two groups in stone size 6 to 10 mm was not statistically significant (p value >.05). Complete stone clearance one month after ESWL in Group A was 13(76%) and Group B was 07(43.75%) for stone size 11 to 15 mm. Comparison of clearance rate between two groups in stone size 11 to 15 mm was statistically significant (p value <.05). In this study requirement of number of ESWL sessions according to the stone size showed, in case of 6 to 10 mm stone size, average ESWL sessions 1.28±0.5 in Group A and 1.53±0.7 in Group B and in case of 11to 15 mm stone size, average ESWL sessions 1.29±0.5 in Group A and 1.62±0.7 in Group B. Comparison of ESWL sessions between two groups were statistically significant (p value <.05). In this study mean expulsion time of stone in Group A was 22.34±12.23 days and in Group B was 32.34±21.96 days. Comparison of stone expulsion time between two groups were statistically significant (p value <.05). Conclusion: Tamsulosin results in increased stone-free rates and in lower percentages of patients requiring re-treatment. Tamsulosin can be self-administered and can play a key role in the choice between tamsulosin after ESWL and only ESWL for upper ureteric stone disease treatment. Use of tamsulosin makes the expulsive medical therapy suitable for improving overall outcomes of ESWL treatment for upper ureteral stones. Tamsulosin helps in clearance of upper ureteral stones after ESWL. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.36-42